Accurate finite element modeling of the mechanical behavior of SS304 across the peak dynamic strain aging temperatures. Issue 3 (3rd July 2022) - Patra, Siddhartha; Dhar, Sankar; Acharyya, Sanjib Kumar
ABSTRACT: Dynamic strain ageing or DSA is exhibited by ferrous and aluminium alloys typically at elevated temperatures and low strain rates. This effect, in association with viscoplasticity, produces a complex material behaviour which is manifested through positive strain rate sensitivity of the flow stress in certain pockets of temperatures and strain rates and negative strain rate sensitivity in others. The conventional material models of DSA either lack the ability to accurately capture the DSA effect or to incorporate the effect of the temperature variation. The objective of this work was to propose a constitutive model which can do both. The desired material model was proposed by performing necessary augmentations to a conventional material model. The suitable conventional model for this purpose was identified through rigorous comparison of the existing models. The proposed constitutive model could accurately capture the DSA behaviour of austenitic stainless steel 304 for different strain rates over a range of temperatures across the peak DSA temperatures.